Laidu Manor House School. Assessment of Cultural Heritage Assets upon Closing of the School - Zilgalvis, Jānis (Landscape Architecture and Art, 2022)
The architecture of Courland manor houses is rich in classical monuments. Many of them form impressive building ensembles. The use of the buildings varies, historically – schools, parish boards, farm administrations, nowadays – guesthouses, private properties and still schools. One such site is in Laidi, where the existence of a school is problematic.